Analytical Modeling of Mass-Sensitive Gas Sensor based on MEMS Resonator - Ahmed, Abdelaziz Yousif (2011)
Modeling of a micromachined MEMS resonator for gas detection is presented in this paper. The principle of detection of the gaseous species is based on the change in resonant frequency of the microcantilever due to change in mass induced by the adsorption of an analyte molecule onto the surface of the active material deposited on the microresonator. The theoretical resonant frequency is found to be 20.1 kHz. The change in the resonant frequency Δf = 0.13 Hz when the mass changes by Δm =43.2 fg on the resonator platform.The sensitivity is theoretical calculated to be0.3 Hz/pg.